Time to blip – stochastic simulation of single channel opening - Thul, Ruediger (Cold Spring Harbor Laboratory Press, 2014)
The stochastic dynamics of the inositol-1,4,5-trisphosphate (IP3) receptor (IP3R) is key to understanding a wide range of observed calcium (Ca2+) signals (Falcke 2004). The stochastic nature results from the constant binding and unbinding of Ca2+ and IP3 to and from their respective binding sites and is especially important in the initiation of a Ca2+ puff, i.e. the release of Ca2+ through a cluster of IP3Rs. Once the first IP3R opens, the Ca2+ concentration rises significantly around the ion channel and hence increases the open probability for neighboring IP3Rs. In turn this may trigger the activation of further receptors giving rise to a Ca2+ puff (Thul et al. 2009; Thurley et al. 2012). In this protocol, we determine the time that it takes for a single IP3R to open from rest. We explicitly take into account the tetrameric structure of the IP3R and the fact that multiple subunits need to be active before the channel opens (Bezprozvanny et al. 1991; Watras et al. 1991). We develop code for a stochastic simulation of the IP3R and simulate it using the software package Matlab (Attaway 2011). This protocol demonstrates the basic form of a stochastic simulation algorithm and may serve as a starting point to investigate more complex gating dynamics.